2013
DOI: 10.1111/ajo.12071
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following selective fetal reduction in monochorionic and dichorionic twin pregnancies discordant for structural, chromosomal and genetic disorders

Abstract: Selective reduction in MC pregnancies carries an increased procedure-related and preterm delivery rate compared with DC pregnancies. The main indication for selective reduction was structural malformations, with a predominance of CNS anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
3
21
1
Order By: Relevance
“…In the study of van den Bos et al [4] and Roman et al [16], RFA was associated with lower survival rates, and Bebbington et al [17] also demonstrated that the overall survival was higher in the bipolar cord occlusion group than in the RFA group, at 85.2 and 70.7%, respectively. Conversely, Nobili et al [18] showed that a higher rate was found in the RFA group than in the BCC group, at 92.3 and 90.9%, respectively. Our data also showed that the survival rates are not significantly higher in the RFA group than in the BCC group, and the survival rates of this study were lower than those declared by Nobili's results [18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study of van den Bos et al [4] and Roman et al [16], RFA was associated with lower survival rates, and Bebbington et al [17] also demonstrated that the overall survival was higher in the bipolar cord occlusion group than in the RFA group, at 85.2 and 70.7%, respectively. Conversely, Nobili et al [18] showed that a higher rate was found in the RFA group than in the BCC group, at 92.3 and 90.9%, respectively. Our data also showed that the survival rates are not significantly higher in the RFA group than in the BCC group, and the survival rates of this study were lower than those declared by Nobili's results [18].…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, Nobili et al [18] showed that a higher rate was found in the RFA group than in the BCC group, at 92.3 and 90.9%, respectively. Our data also showed that the survival rates are not significantly higher in the RFA group than in the BCC group, and the survival rates of this study were lower than those declared by Nobili's results [18]. In Bebbington's report [17], preterm delivery (<34 weeks), pPROM, birth weight and neonatal demise were also not significantly different between these 2 modalities.…”
Section: Discussionmentioning
confidence: 98%
“…SR via intravascular KCl injection is the primary method for selective feticide in dichorionic twins [1], but is contraindicated in monochorionic, diamniotic twin gestations due to the increased risk of co-twin injury or death [2]. There are several potential mechanisms for co-twin injury after intravascular KCl injection in monochorionic twins.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is less invasive, as KCl injection is typically performed with a 22-gauge needle, while cord occlusion requires a probe (17-18 G) or endoscope (up to 3.8 mm in diameter) to complete [8]. These advantages may translate into lower risks and improved outcomes [2]. The fetal loss rate (miscarriage before 24 weeks) after SR of a discordant anomalous dichorionic twin via intravascular KCl injection is approximately 7.5%, although this rate varies by two percentage points depending on the gestational age the procedure is carried out [9].…”
Section: Discussionmentioning
confidence: 99%
“…About one half of those pregnancies are uneventful, but the other half may be complicated by twin-totwin transfusion syndrome (TTTS), selective fetal growth restriction (sFGR), twin reversed arterial perfusion (TRAP) sequence or discordance for fetal abnormality (DFA). In the most severe forms of those complications, when one fetus is severely anomalous, or is suffering severe distress, particularly if the condition is compromising the non-affected fetus, selective fetal termination (SFT) may be the best option, as in the case of single intrauterine death of one fetus, profound consequences for the surviving twin are reported, including a 15-25% risk of death or neurological damage [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%